2017
DOI: 10.5056/jnm16178
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Salivary Pepsin Concentration and Esophageal Mucosal Integrity in Patients With Gastroesophageal Reflux Disease

Abstract: Background/AimsIncreased salivary pepsin could indicate an increase in gastro-esophageal reflux, however, previous studies failed to demonstrate a correlation between salivary pepsin concentrations and 24-hour esophageal acid exposure. This study aims to detect the salivary pepsin and to evaluate the relationship between salivary pepsin concentrations and intercellular spaces (IS) in different gastroesophageal reflux disease phenotypes in patients. MethodsA total of 45 patients and 11 healthy volunteers were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
9
0
3
Order By: Relevance
“…Esophageal mucosal damage is caused by the reflux of gastric acid and stomach contents, which is related to the inflammation process and might lead to esophageal stenosis and cancer in the esophagus [ 3 , 32 ]. To evaluate the protective effects of DGK on RE rats, experimental rats were orally administrated with DICHO fraction (100 and 200 mg/kg body weight).…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal mucosal damage is caused by the reflux of gastric acid and stomach contents, which is related to the inflammation process and might lead to esophageal stenosis and cancer in the esophagus [ 3 , 32 ]. To evaluate the protective effects of DGK on RE rats, experimental rats were orally administrated with DICHO fraction (100 and 200 mg/kg body weight).…”
Section: Discussionmentioning
confidence: 99%
“…Pepsin is the key aggressive enzyme in the gastric juice and is a vital biomarker used in the diagnosis of GERD …”
Section: Introductionmentioning
confidence: 99%
“…51 Previous studies have shown that esophageal and throat tissues were sensitive to pepsin, and a small amount of activated pepsin could cause inflammation in the mucosa of the esophagus and throat, thus causing subjective discomfort and symptoms. [52][53][54] A previous study by Li et al 55 showed that the intercellular spaces measurements were greater in EE and NERD groups than in FH and HC groups. Patients with NERD had a higher level of salivary pepsin compared to those with FH.…”
Section: Discussionmentioning
confidence: 91%